Screening for psychiatric morbidity in the population - a comparison of the GHQ-12 and self-reported medication use - Tseliou, Foteini; Donnelly, Michael; O'Reilly, Dermot (International Journal of Population Data Science, 2018)
Introduction Uptake of psychotropic medication has been previously used as a proxy for assessing the prevalence of population mental health morbidity. However, it is not known how this compares with estimates derived from population screening tools. Objectives To compare estimates of psychiatric morbidity derived by a validated screening instrument of psychiatric morbidity and a self-reported medication uptake measure. Methods This study used data from two recent population-wide health surveys in Northern Ireland, a country (UK) with free health services and no prescription charges. The psychiatric morbidity of 7,489 respondents was assessed using the GHQ-12 and self-reported use of medication for stress, anxiety and depression (sDAS medication). Results Overall, 19% of respondents were defined as ‘cases’ and 14.3% were taking sDAS medication. Generally, the two methods identified the same population distributions of characteristics that were associated with psychiatric morbidity though nearly as many non-cases as cases received sDAS medication (46.4% vs. 53.6%). A greater proportion of women and older people were identified as cases according to sDAS medication use, while no such variation was observed between socio-economic status and method of assessment. Conclusions This study indicates that these two methods of assessing population psychiatric morbidity provide similar estimates, despite potentially identifying different individuals as cases. It is important to note that different health care systems might be linked to variations in obstacles when accessing and using health care services. Highlights There was a reasonable correspondence between the different methods of assessment. A greater proportion of women and older people were identified as cases through the self-reported use of medication. An almost equal amount of GHQ-12 cases and non-cases reported being in receipt of medication.